2024
DOI: 10.1556/2055.2022.00028
|View full text |Cite
|
Sign up to set email alerts
|

When social status gets in the way of reproduction in modern settings: An evolutionary mismatch perspective

Abstract: Low fertility is a growing concern in modern societies. While economic and structural explanations of reproductive hindrances have been informative to some extent, they do not address the fundamental motives that underlie reproductive decisions and are inadequate to explain why East Asian countries, in particular, have such low fertility rates. The current paper advances a novel account of low fertility in modern contexts by describing how modern environments produce a mismatch between our evolved mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 140 publications
(227 reference statements)
0
4
0
Order By: Relevance
“…The modern environment seems to trigger short-term ambitions even in lower-value men-as they witness the mating success of the most attractive men-which was the case with Sigurd. Yong et al (2023) found that not only insings but also lower-value men are adopting unrealistic standards that prevent pair bonding. Mating opportunities may be increasingly channeled to the most attractive men, but also other men respond to our present era's promiscuity with a choosiness that makes it even harder for them to find a mate.…”
Section: Is Dating Mastery Only For Douches?mentioning
confidence: 99%
See 1 more Smart Citation
“…The modern environment seems to trigger short-term ambitions even in lower-value men-as they witness the mating success of the most attractive men-which was the case with Sigurd. Yong et al (2023) found that not only insings but also lower-value men are adopting unrealistic standards that prevent pair bonding. Mating opportunities may be increasingly channeled to the most attractive men, but also other men respond to our present era's promiscuity with a choosiness that makes it even harder for them to find a mate.…”
Section: Is Dating Mastery Only For Douches?mentioning
confidence: 99%
“…Not only does this societal evolution impose existential pain on men unable to live up to cultural ideals, but also some of them respond maladaptively. Yong et al (2023) found that men with low mate value, instead of accepting that an assortative, long-term strategy is their best bet, approach mating markets with unrealistic expectations. Those men who do get into pair bond may also suffer increased psychological pressures.…”
Section: Comparing Mating Victimizationmentioning
confidence: 99%
“…Not only does this societal evolution impose existential pain on men unable to live up to cultural ideals, but also some of them respond maladaptively. Yong et al (2023) found that men with low mate value, instead of accepting that an assortative, long-term strategy is their best bet, approach mating markets with unrealistic expectations. Those men who do get into pair bond may also suffer increased psychological pressures.…”
Section: Comparing Mating Victimizationmentioning
confidence: 99%
“…The modern environment seems to trigger short-term ambitions even in lower-value men-as they witness the mating success of the most attractive men-which was the case with Sigurd. Yong et al (2023) found that not only insings but also lower-value men are adopting unrealistic standards that prevent pair bonding. Mating opportunities may be increasingly channeled to the most attractive men, but also other men respond to our present era's promiscuity with a choosiness that makes it even harder for them to find a mate.…”
Section: Is Dating Mastery Only For Douches?mentioning
confidence: 99%